InHabit people, places and possessions - Buxton, Antony; Hulin, Linda; Anderson, Jane Estelle (Peter Lang, 2017)
Central to human life and experience, habitation forms a context for enquiry within many disciplines. This collection brings together perpectives on human habitation from fields such as archaeology, material culture, art and design, and architecture, providing compelling examples of the potential for interdisciplinary conversations on the subject
Keywords: Human geography--Philosophy; Lebensführung; Stadtforschung; Aufsatzsammlung